Analysis of the forces in the construction of large-span steel box girder by incremental construction. Issue 1 (October 2020) - Zhuoqun, Chen; Zongrun, Rao; Ming, Li; Jiaqi, Bi
Abstract: Taking a large-span steel curved bridge in Yunnan Province as the research object, this paper focuses on the multi-point jacking construction technology and construction control points, which provides the basis for the limited jacking construction planning and reasonable arrangement of working procedures in Yunnan Province. Taking the successful application of a large-span steel box girder on the pusher as an example, the numerical simulation of the steel pushing process is carried out by using the finite element software 3D3S, and the data analysis of the structure is summarized in this paper, which provides reference for solving similar engineering problems in the future.